Social network and participation in elderly primary care patients in Germany and associations with depressive symptoms: a cross-cectional analysis from the AgeWell.de study - Wendel, Flora; Bauer, Alexander; Blotenberg, Iris; Brettschneider, Christian; Buchholz, Maresa; Czock, David; Döhring, Juliane; Escales, Catharina; Frese, Thomas; Hoffmann, Wolfgang; Kaduszkiewicz, Hanna; König, Hans-Helmut; et al. (Journal of Clinical Medicine, 2022)
This study aims to describe social network and social participation and to assess associations with depressive symptoms in older persons with increased risk for dementia in Germany. We conducted a cross-sectional observational study in primary care patients (aged 60-77) as part of a multicenter cluster-randomized controlled trial (AgeWell.de). We present descriptive and multivariate analyses for social networks (Lubben Social Network Scale and subscales) and social participation (item list of social activities) and analyze associations of these variables with depressive symptoms (Geriatric Depression Scale). Of 1030 included patients, 17.2% were at risk for social isolation (Lubben Social Network Scale < 12). Looking at the subscales, a reduced non-family network was found almost twice as often as a reduced family network. Patients with depressive symptoms had significantly smaller social networks than patients without depression (p < 0.001). They rather engaged in social activities of low involvement level or no weekly social activity at all (p < 0.001). The study shows associations of depressive symptoms with a decreased social network and less social participation in elderly participants. Sufficient non-family contacts and weekly social activities seem to play an important role in mental health and should be encouraged in elderly primary care patients.
Gesehen am 11.01.2023